Comparison of the Influence of Vegetarian and Mediterranean Diets on the Formation of Kidney Stones - Sebastian Samuła; Michał Mazur; Dorota Waz; Jakub Szarłowicz; Zofia Goliszek; Karolina Łucja Sobek; Wiktoria Tabin-Barczak; Aldona Sokołowska; Klaudia Fikas; Kamil Chwaliszewski (Quality in Sport)
Introduction and Purpose: